Clinical Significance of Mucin Extravasation in Breast Core Biopsy Specimens - Begum, SM Khodeza Nahar; Richelia, Jara Lazaro Ana; Thike, Aye Aye; Ho, Julian Teng-Swan; Wong, Jill Su-Lin; Tan, Puay Hoon (Anwer Khan Modern Medical College Journal, 2011)
Mucin extravasation (ME) refers to the presence of mucin pools in the breast parenchyma, usually resulting from ruptured ducts distended with luminal mucin. Extravasated mucin is usually seen along with cystically dilated mucin filled ducts or mucocele like lesions (MLL) of the breast. MLL is a rare lesion that may be associated with a continuum of benignity to invasive mucinous carcinoma. The purpose of this study was to document the spectrum of lesions that can be associated with ME in breast cores and to correlate with the histology in subsequent surgical excision. Thirty-seven cases with ME on image guided core biopsies were reviewed from our departmental files, and their radiologic histologic findings were noted. Twenty-six of them of them underwent subsequent open biopsies which forms the basis of this study. It was noticed that columner cell lesion (CCL) associated with mucocele like lesion (MLL) as an important finding in relation with atypia. This finding was significant regardless of their presence in calcified or non-calcified cores and also a very good statistical correlation was seen between the quantitative presence of CCL in the core and excisional biopsy diagnosis. This are support the need for excision biopsy for the cases presenting with ME in their cores. In addition, a multidisciplinary approach should also be taken for cases presenting with ME, MLL and CCL altogether in breast core biopsies even in absence of obvious cytological atypia. Key Words: Mucin ExtravasationL Columnan Cell Lesion (CCL); Mucocele Like Lesion (MLL); Fibrocystic Change (FCC); Atypical Ductal Hyperplasia (ADH); Ductal Carcinoma in Situ (DCIS) DOI: 10.3329/akmmcj.v2i1.7466 Anwer Khan Modern Medical College Journal 2011; 2(1): 15-21